Master microservices with Spring Boot and Spring Cloud - Karanam, Ranga (Packt Publishing, 2018)
"Developing RESTful web services is fun. The combination of Spring Boot, Spring Web MVC, Spring Web Services, and JPA makes it even more fun. And it's even more fun to create Microservices. There are two parts to this course - RESTful web services and Microservices. Architectures are moving towards Microservices. RESTful web services are the first step to developing great Microservices. Spring Boot, in combination with Spring Web MVC (also called Spring REST) makes it easy to develop RESTful web services. In the first part of the course, you will learn the basics of RESTful web services developing resources for a social media application. You will learn how to implement these resources with multiple features including versioning, exception handling, documentation (Swagger), basic authentication (Spring Security), filtering, and HATEOAS. You will learn the best practices in designing RESTful web services. In this part of the course, you will be using Spring (Dependency Management), Spring MVC (or Spring REST), Spring Boot, Spring Security (Authentication and Authorization), Spring Boot Actuator (Monitoring), Swagger (Documentation), Maven (dependencies management), Eclipse (IDE), Postman (REST Services Client), and the Tomcat embedded web server. We will help you set up each one of these. In the second part of the course, you will learn the basics of Microservices. You will understand how to implement Microservices using Spring Cloud. In this part of the course, you will learn how to establish communication between Microservices, enable load balancing, and the scaling up and down of Microservices. You will also learn to centralize the configuration of Microservices with Spring Cloud config server. You will implement the Eureka naming server and distributed tracing with Spring Cloud Sleuth, and Zipkin. You will create fault-tolerant Microservices with Zipkin."--Resource description page